Development and Validation of a Questionnaire to Assess Creative Potential Traits - Penagos-Corzo, Julio C.; Saucedo, Axel (Frontiers in Psychology, 2021)
The aim of the study was to develop an inventory to assess traits of creative potential and to analyze its psychometric properties. Three dimensions that could be associated with creative potential were proposed: willingness to transgress, willingness to take on challenges, and willingness to explore. For this purpose 551 participants were chosen to respond to an inventory composed of 12 items: Traits of Creative Potential Questionnaire, (TCPQ-12) and other tests to determine concurrent validity. The correlations between these instruments were significant. In addition, the instrument showed adequate internal consistency (Ω = 0.813) and the exploratory factor analysis yielded salient factors coincident with the proposed dimensions. The confirmatory factor analysis indicated an optimal fit (CFI = .984). The study data allow to highlight that the instrument presented here is a concise instrument with adequate psychometric properties..